2021
DOI: 10.3389/fncel.2020.606687
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Native Hyperpolarization-Activated, Cyclic Nucleotide-Gated Channel Function by the Volatile Anesthetic Sevoflurane in Mouse Thalamocortical Relay Neurons

Abstract: As thalamocortical relay neurons are ascribed a crucial role in signal propagation and information processing, they have attracted considerable attention as potential targets for anesthetic modulation. In this study, we analyzed the effects of different concentrations of sevoflurane on the excitability of thalamocortical relay neurons and hyperpolarization-activated, cyclic-nucleotide gated (HCN) channels, which play a decisive role in regulating membrane properties and rhythmic oscillatory activity. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
(149 reference statements)
0
6
0
Order By: Relevance
“…Our findings suggest that cGMP/HCN signaling partially mediates volatile anesthetic actions on presynaptic function in hippocampal neurons. Previous studies have implicated HCN in anesthetic mechanisms in thalamic 34 , thalamocortical 35 , and forebrain neurons 36 . HCN channels can be gated by either cAMP or cGMP; our study is the first to link volatile anesthetic depression of cGMP production with reduced HCN function.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that cGMP/HCN signaling partially mediates volatile anesthetic actions on presynaptic function in hippocampal neurons. Previous studies have implicated HCN in anesthetic mechanisms in thalamic 34 , thalamocortical 35 , and forebrain neurons 36 . HCN channels can be gated by either cAMP or cGMP; our study is the first to link volatile anesthetic depression of cGMP production with reduced HCN function.…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane, as a common inhalation anesthetic, is widely used in the field of anesthesiology over the world. HCN channels as the target for sevoflurane were sufficiently established by our team and other researchers [ 18 , 19 ]. To the best of our knowledge, this study was the first report to demonstrate that sevoflurane acts on its target-HCN2 channel to regulate microglial function and neuroinflammation in vivo, triggering cognitive impairment and anxiety-like behaviors in rats.…”
Section: Discussionmentioning
confidence: 99%
“…We and others found that sevoflurane, as a volatile anesthetic, can inhibit hyperpolarization-activated, cyclic nucleotide-gated (HCN) channels, and HCN knockout or selective HCN channel blocker ZD7288 can increase anesthetic properties of sevoflurane [ 18 , 19 ]. Interestingly, an in vitro experiment has provided the novel discovery that HCN channels can be expressed on primary microglia and contribute to various microglial functions and influence the course of microglial activation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pyramidal neurons in the cortical lamina IV were identified due to optically evoked EPSP to optogenetic stimulation of thalamocortical relay neurons and by visual control (Feldmeyer, 2012 ). Thalamocortical relay neurons of the thalamic ventrobasal complex were identified visually and by means of their unique electrophysiologic properties (Schwerin et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%